Rekonstruksi Lintasan Objek Bergerak Pada Citra Digital Video Dengan Metode Belief Propagation - Efron Manik (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2021)
The control device in an auto-navigation car is a computer assisted by two cameras on the front of the car to determine the three-dimensional coordinates of all pixels of the digital image captured by the camera from frame to frame. So that the computer will be able to determine where the streets are flat or potholes. The purpose of this research is to create a program code that is able to determine the disparity from one frame to the next. With the help of recordings from two cameras, the disparity of any object captured on the two cameras will be calculated for each pixel. This data is used to compare the accuracy of the methods developed in this study. We use a program code developed to calculate the disparity of each frame in the video. The model developed in this study still needs to be studied in order to find a better method.